2019
DOI: 10.38061/idunas.629389
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Antimalarial and Antimicrobial activities of Mixed Ibuprofen-Pyrimethamine M(II) Complexes [M = Cd, Co, Zn, Mn]

Abstract: Mixed complexes of Ibuprofen-Pyrimethamine were synthesized using Cd(II) Co(II), Zn(II), and Mn(II). The mixed complexes were characterized based on some physicochemical and spectroscopic techniques such as infrared, elemental analysis, conductivity measurements, and magnetic moment. Based on the results obtained, the complexes were formulated as [M(L1)(L2)]Cl2, where M = metal ion, L1 = Pyrimethamine, L2 = Ibuprofen). The complexes were found to be non-electrolytes. The ligands act as bidentate towards the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…The proposed structure of the complexes are displayed in Figure 1. The elemental analysis indicated that the theoretical and experimental are in good agreement with each other 13,21,22 . They are stable at room temperature and in powdery form with melting point greater than 360ºC.…”
Section: Chemistry Of the Complexessupporting
confidence: 62%
See 3 more Smart Citations
“…The proposed structure of the complexes are displayed in Figure 1. The elemental analysis indicated that the theoretical and experimental are in good agreement with each other 13,21,22 . They are stable at room temperature and in powdery form with melting point greater than 360ºC.…”
Section: Chemistry Of the Complexessupporting
confidence: 62%
“…The decomposition temperature for the complexes were greater than 360 ℃. The molar conductance of the complexes are 70, 85, and 87 Ω -1 cm 2 mol -1 for Mn(II), Cu(II), and Cd(II) complexes respectively indicating that they are electrolytic in nature, while Ni(II) complex with a molar conductance of 24 Ω -1 cm 2 mol -1 is non-electrolyte 12,21,23 and [Mn(ANT)(AMO)Cl 2 ] complexes were found in an octahedral environment, [Ni(ANT)(AMO)] complex exhibited square planar geometry [11][12][13][14]21,24 . Hence, the proposed synthetic equation for the metal drug complexes can be shown as:…”
Section: Chemistry Of the Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] Hence, they are the essential compounds in the field of biochemistry and pharmaceutical chemistry. They are mostly used as potential drugs in the form of anti-cancer, [15][16][17][18][19] anti-microbial, [20][21][22][23][24] anti-tumour, [25,26] antimalarial, [27][28][29][30][31][32] anti-inflammatory, [33,34] anti-oxidant, [35][36][37][38][39] antipyret-ic agents, [40,41] etc. The bio-compatibility of Schiff base compounds is due to their ability to bind with the DNA.…”
Section: Introductionmentioning
confidence: 99%